Preparation of polymeric macroporous rod systems: Study of the influence of the reaction parameters on the porous properties - Arrua, Ruben Dario (2008)
Polymeric macroporous rod systems were prepared using N-acryloyl-tris(hydroxymethyl)aminomethane (NAT) and glycidyl methacrylate (GMA) as mono-vinyl monomers and N,N -methylenebisacrylamide (BIS) or trimethylolpropane trimethacrylate (TRIM) as crosslinking agents. The reactions were performed in the presence of a ternary porogenic diluent (composed by dimethylsulfoxide, tetradecanol and poly(ethylenglycol) 6000 (PEG 6000)) and azobisisobutyronitrile (AIBN) as initiator, by freeradical crosslinking copolymerization. The effect of polymerization temperature, porogenic mixture and crosslinker was analyzed. The results showed that a lower polymerization temperature and an increase in the amount of non-solvating diluents (tetradecanol and PEG 6000) in the reaction mixture led to products with higher porosity. The prepared monoliths were promising as potential base supports for different chromatography processes, especially those synthesized with GMA, since its incorporation allows to bind different ligands in a direct coupling reaction.